Team topologies organizing business and technology teams for fast flow - Skelton, Matthew 1971-; Pais, Manuel 1970- (IT Revolution, 2019)
"In Team Topologies, DevOps consultants Matthew Skelton and Manuel Pais share secrets of successful team patterns and interactions to help IT organizations choose and evolve the right team patterns to ensure success, making sure to keep the software healthy and to optimize for value streams. Team Topologies will help readers discover: - Team patterns used by successful organizations. - Common team patterns to avoid with modern software systems. - When and why to use different team patterns - How to evolve teams effectively. - How to split software and align to teams"--
Includes bibliographical references and index
Keywords: Organisation; Teamwork; Information technology / Management; Teams in the workplace / Management; Computer software / Development / Management